2021
DOI: 10.1039/d1na00591j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into the anisotropic growth of ZnO nanoparticles deciphered through 2D size plots and multivariate analysis

Abstract: The control and understanding of the nucleation and growth of nano-objects is a key point for improving and/or considering new applications of a given material at the nanoscale. Mastering the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…[ 60 ] The fast hydrolysis of Zn(Cy) 2 solubilized in various organic solvents (THF, pentane, etc.) takes place with one equivalent of water in the presence of dodecylamine (C 12 H 27 N, DDA), [ 61 ] a suitable ligand for ZnO. Note that the ligand may also play a role on the hydrolysis reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 60 ] The fast hydrolysis of Zn(Cy) 2 solubilized in various organic solvents (THF, pentane, etc.) takes place with one equivalent of water in the presence of dodecylamine (C 12 H 27 N, DDA), [ 61 ] a suitable ligand for ZnO. Note that the ligand may also play a role on the hydrolysis reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The reported analogous synthesis of ZnO NPs are classically prepared in batch processes in solution using Schlenk tube glassware, [ 60 , 61 ] needing at least one equiv. of DDA to achieve the colloidal stabilization in THF solution.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have compared the effect of alkylamine chain‐length on the growth of ZnO nanorods, using alkylamines such as octylamine (C8) up to oleylamine (C18). [ 46,47 ] They found that the alkylamines adsorb onto the nonpolar side facets of ZnO promoting oriented growth along the c ‐axis, similar to the behavior of other amines, with increased growth occurring more as chain length increased. This is a result of complex formation between Zn 2+ and the alkylamine, which showed increasing stability with longer carbon chains.…”
Section: Introductionmentioning
confidence: 87%
“…As mentioned above, the organometallic precursor's character can play a significant role in the nucleation, growth and quality of the final QDs. 71,72 Diorganozinc compounds have been known to easily form the Lewis-acid adducts with lowmolecular-weight neutral donors [73][74][75][76][77] and the adduct formation strongly affects the reactivity of zinc alkyls towards water 78 and dioxygen. 76 Thus, we were curious to what extent DMF and sulfoxides as Lewis bases could be suitable candidates for tuning the reactivity of dialkylzinc compounds as auxiliary ligands.…”
Section: One-pot L-type Protector-assisted Synthesis Of Zno Qdsmentioning
confidence: 99%